Coastal uplift rate at Matanzas (Cuba) inferred from MIS5e phreatic overgrowths on speleothems. (20th January 2017) - De Waele, Jo; D'Angeli, Ilenia M.; Tisato, Nicola; Tuccimei, Paola; Soligo, Michele; Ginés, Joaquín; Ginés, Angel; Fornós, Joan J.; Villa, Igor M.; Grau González, Esteban R.; Bernasconi, Stefano M.; Bontognali, Tomaso R. R.
Abstract: Many morphological elements in Cuba's landscape (e.g. marine terraces, tidal notches) demonstrate that coastal uplift has taken place, but the rate at which this occurs is not known. Carbonate phreatic overgrowths on speleothems have been found in a cave in Central North Cuba, ~1 km from the present coastline at 16 m asl. They form exceptional and unique mushroom‐shaped speleothems and balconies decorating the walls of the rooms. These phreatic overgrowths on speleothems (POS) formed at the oscillating air–water interface in sea‐level controlled anchialine lakes. U/Th dating of these overgrowths suggests ages that are compatible with the Marine Isotope Stage 5e (i.e. 130–115 ka). These POS have fixed this sea‐level highstand and demonstrate that this part of Cuba has been subjected to a much lower uplift rate than previously reported, that is, less than 0.1 mm/year since the last interglacial.